Tobacco- and alcohol-attributable burden of early-onset lip, oral cavity, and pharyngeal cancer in 204 countries and territories from 1990 to 2019, with projections to 2040 - Dai, Xingzhu; Liang, Yuanhao (Frontiers in Oncology, 2024)
BackgroundRising trends in early-onset Lip and oral cavity cancer (LOC) and Other pharyngeal cancer (OPC) burden had been observed. This study aimed to evaluate the burdens of LOC and OPC attributable to tobacco and alcohol in young adults aged 15-49 years from 1990 to 2040.MethodsTobacco- and alcohol-attributable death and disability-adjusted life years (DALYs) for LOC and OPC and the corresponding population-attributable fraction were obtained from Global Burden of Disease Study 2019 for individuals aged 15-49 years. Estimated annual percent change was calculated to quantify the temporal trend of disease burden between 1990 and 2019. The Bayesian age-period-cohort model was used to predict the age-standardized mortality rate from 2020 to 2040.ResultsIn 2019, an estimated 16,887 deaths and 799,495 DALYs for tobacco- and alcohol-attributable early-onset LOC, and 8,402 deaths and 386,418 DALYs for early-onset OPC attributable to tobacco and alcohol were reported globally. Despite the global decrease in age-standardized mortality and DALYs rates of tobacco- and alcohol-attributable LOC and OPC in young adults aged 15-49 years between 1990 and 2019, certain regions experienced increases, such as regions of Asia, Eastern Europe, and Western Sub-Saharan Africa. Moreover, a growing age-standardized mortality in individuals aged <34 years was found. The socio-demographic index level was positively associated with a faster reduction of early-onset LOC and OPC DALYs attributable to alcohol use and smoking, except for that due to chewing tobacco. Furthermore, projections have also indicated an expected increase in the age-standardized mortality for tobacco- and alcohol-attributable early-onset LOC and OPC.ConclusionsSignificant regional and demographic disparities in tobacco and alcohol-related early-onset LOC and OPC burden and their attributable proportion highlight a need for tailored age- and region-appropriate interventions to reduce the future LOC and OPC burden among young adults.